PENGARUH KEMAMPUAN BERPIKIR KRITIS TERHADAP KEMAMPUAN MENYELESAIKAN MASALAH BELAJAR SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPAS DI SDN GUNUNGSARI - Wardani, Dwi Kumala; Sakdiyah, Siti Halimatus; Kumala, Farida Nur; Indawati, Ninik (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2024)
Critical thinking skills are currently very important for students to have. Critical thinking skills are one of the four main skills in the 21st century, namely communication, collaboration, critical thinking, and creativity. The purpose of this study is to determine the influence of critical thinking skills on the ability to solve learning problems of elementary school students in science and science learning. This research method is a quantitative experiment using a quantitative research approach. The population of this study is all class IV students totaling 20 students and the sample uses a probability sampling technique with random sample sampling. The instruments used in this study used an essay test of critical thinking skills and problem-solving skills as many as 20 questions. The data analysis technique used is simple linear regression. The results of the study show that grade IV elementary school students have been able to apply critical thinking skills to students' ability to solve learning problems in science and science learning, this is evident from students' ability to understand and analyze the root cause of problems, find solutions in depth, filter out true and false information, and make decisions based on logic and evidence. Based on the hypothesis test using a simple linear regression equation test, a tcal value of 2,450 > a table of 1,734 was obtained, and it can be concluded that critical thinking ability has a significant effect on problem-solving ability.